2003
DOI: 10.1038/sj.leu.2402901
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antiproliferative activity of the farnesyltransferase inhibitor R115777 in hematopoietic progenitors from patients with myelofibrosis with myeloid metaplasia

Abstract: R115777 is an orally bioavailable farnesyltransferase inhibitor (FTI) that has displayed encouraging activity in patients with acute myeloid leukemia. To determine whether R115777 might exert similar activity in myelofibrosis with myeloid metaplasia (MMM), we evaluated its effects on circulating myeloid progenitor cells from patients with MMM (n ¼ 25) using in vitro colony-forming assays. The median R115777 concentrations that inhibited colony formation by 50% were 34 and 2.7 nM for myeloid and megakaryocytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 45 publications
0
24
1
Order By: Relevance
“…R115777, a farnesyl transferase inhibitor, has shown in vitro antiproliferative activity in the haemopoietic progenitors from IM patients (Mesa et al, 2003b). In a trial including eight patients, this drug provided 25% favourable responses in anaemia and splenomegaly, with the responses being significantly associated with higher VEGF plasma levels at the start of treatment (Cortes et al, 2003b).…”
Section: Imatinib and Other New Drugsmentioning
confidence: 99%
“…R115777, a farnesyl transferase inhibitor, has shown in vitro antiproliferative activity in the haemopoietic progenitors from IM patients (Mesa et al, 2003b). In a trial including eight patients, this drug provided 25% favourable responses in anaemia and splenomegaly, with the responses being significantly associated with higher VEGF plasma levels at the start of treatment (Cortes et al, 2003b).…”
Section: Imatinib and Other New Drugsmentioning
confidence: 99%
“…Dose-response curves before initiating therapy showed a median IC 50 of 11.8 nM tipifarnib (range: 0.5-200 nM), which is slightly lower than the IC 50 of 34 nM tipifarnib (range: 7.5-74.5 nM) we previously reported in myeloid progenitors from PMF patients. 24 Although progenitors from nine patients (27%) in the current group exhibited a pretreatment IC 50 434 nM, Further analysis indicated that clinical response to tipifarnib was not significantly correlated with baseline myeloid colony growth or ex vivo tipifarnib sensitivity (IC 50 values) (Wilcoxon rank-sum test). When results of the serial ex vivo dose-response curves were examined, circulating progenitors from seven patients demonstrated decreased sensitivity to tipifarnib in vitro (a 450% increase in IC 50 range (78-5120%)), while progenitors from five displayed an increase in tipifarnib in vitro sensitivity (a 450% decrease in IC 50 range (56-89%), Figure 1).…”
Section: Correlations Of Clinical Response and Ex Vivo Tipifarnib Senmentioning
confidence: 99%
“…Paired samples harvested before and during tipifarnib therapy from 20 patients were examined for tipifarnib sensitivity ex vivo using the methodology we have described previously. 24 Briefly, aliquots containing 600 000 PBMCs (2 Â 10 6 /ml) were placed in Methocult (StemCell Technology; Vancouver, BC, Canada) containing diluent or graded drug concentrations (0-100 nM of tipifarnib) and plated as described above. After a 14-day incubation, progenitor colony numbers and subtypes were counted by light microscopy.…”
Section: Assessment Of Response -Clinicalmentioning
confidence: 99%
See 2 more Smart Citations